Recent Advances in Magnetic Microfluidic Biosensors - Giouroudi, Ioanna (Nanomaterials (Basel), 2017)
The development of portable biosening devices for the detection of biological entities such as biomolecules, pathogens, and cells has become extremely significant over the past years. Scientific research, driven by the promise for miniaturization and integration of complex laboratory equipment on inexpensive, reliable, and accurate devices, has successfully shifted several analytical and diagnostic methods to the submillimeter scale. The miniaturization process was made possible with the birth of microfluidics, a technology that could confine, manipulate, and mix very small volumes of liquids on devices integrated on standard silicon technology chips. Such devices are then directly translating the presence of these entities into an electronic signal that can be read out with a portable instrumentation. For the aforementioned tasks, the use of magnetic markers (magnetic particles—MPs—functionalized with ligands) in combination with the application of magnetic fields is being strongly investigated by research groups worldwide. The greatest merits of using magnetic fields are that they can be applied either externally or from integrated microconductors and they can be well-tuned by adjusting the applied current on the microconductors. Moreover, the magnetic markers can be manipulated inside microfluidic channels by high gradient magnetic fields that can in turn be detected by magnetic sensors. All the above make this technology an ideal candidate for the development of such microfluidic biosensors. In this review, focus is given only to very recent advances in biosensors that use microfluidics in combination with magnetic sensors and magnetic markers/nanoparticles.